The impact of role conflict on turnover intention among faculty members: A moderated mediation model of emotional exhaustion and workplace relational conflict - Asfahani, Ahmed M. (Frontiers in Psychology, 2022)
This study examines the impact of emotional exhaustion on faculty role conflict as a source of stress that leads to turnover intention, which is considered to be an undesirable organizational behavior. Drawing on conservation of resources and job-demand theories, the study investigates the moderating effect of workplace relational conflict on the relationships between role conflict among faculty members and both emotional exhaustion and turnover intention. Cross-sectional survey data were collected from 321 faculty members employed in 58 Saudi universities and institutions of higher education. Structural equation modeling revealed that emotional exhaustion mediates the significant positive relationship between faculty members’ role conflict and their turnover intention and that these mediating effects are enhanced by the moderating effect of workplace relational conflict on the significant positive relationship between emotional exhaustion and turnover intention. Unexpectedly, the moderating effect of workplace relational conflict on the relationship between role conflict and emotional exhaustion was not supported by the results. The study concludes by highlighting several theoretical and practical implications and providing suggestions for future research.